2019
DOI: 10.1186/s12871-019-0730-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure pulmonary edema: a case report

Abstract: Background The negative pressure pulmonary edema is rare clinical situation which caused mainly by upper airway obstruction. However except upper airway obstruction, there may be other pathophysiological disorders making patients more vulnerable to pulmonary edema. Based on these disorders, upper airway obstruction is the trigger to induce negative pressure pulmonary edema. Case presentation This case was a 5-year-old girl with tumor on saddle area, her hormones level w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“… 6 The clinical syndromes can usually improves after 12-24 hours. 7 But in our case, the symptoms were improved within 4 hours without any abnormalities. Patients with NPPE history should be kept in mind and prevention methods can be performed accordingly.…”
Section: Discussionmentioning
confidence: 40%
“… 6 The clinical syndromes can usually improves after 12-24 hours. 7 But in our case, the symptoms were improved within 4 hours without any abnormalities. Patients with NPPE history should be kept in mind and prevention methods can be performed accordingly.…”
Section: Discussionmentioning
confidence: 40%
“…10 Type II NPPE usually occurs after relief of chronic airway obstruction, for example, after the operation of tonsillar hypertrophy, adenoid hypertrophy and upper respiratory tract tumours. 12,13 The incidence of NPPE is between 0.1 and 11%, 11,14,15 and it has been reported that the incidence of NPPE in China is as high as 9.6%. 16 The most common cause of NPPE in adults is the laryngospasm after extubation under general anaesthesia, with an incidence of 3% 11,12 ; but the cause of NPPE in children is different from that in adults, which is mainly due to airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of NPPE mainly depends on the history of foreign body inhalation, clinical manifestation and imaging features of pulmonary oedema. 12,13,15,17 Differential diagnosis between NPPE and the following diseases should be in consideration: cardiogenic pulmonary oedema caused by cardiac disease, low colloidal osmotic pulmonary oedema caused by hypoproteinemia, neurogenic pulmonary oedema caused by craniocerebral trauma or virus infection, allergic pulmonary oedema and aspiration pneumonia. None of the three children in this study had aforementioned diseases and were in good health before the airway foreign body obstruction.…”
mentioning
confidence: 99%
“…Along with hypothyriodism, hypocortisolism also occurred in the two cases. Patients with hypocortisolism might be suspected to be more vulnerable to lung leaking syndrome [14], because cortisol may decrease capillary permeability and ameliorate lung endothelial barrier dysfunction. Both mechanisms are strongly associated with mortality of septic shock [15,16].…”
Section: Laboratory Tests Identified Hypothyroidism and Hypocortisolemiamentioning
confidence: 99%